PERIODICITY OF EXPOSURE OF HYDROPONIC LETTUCE PLANTS TO NUTRIENT SOLUTION - Dalastra, Cleiton [UNESP] (2020)
A balanced periodicity of the nutrient solution flow is essential for better agronomic performances and low production costs in hydroponic systems. Thus, the objective of this work was to evaluate the effect of periodicity of exposure of lettuce plants to the nutrient solution in an NFT hydroponic system on the production, nutrition, and profitability of this crop. The experiment was conducted in a randomized block design with five replications. The treatments consisted of four periodicities of exposure of lettuce plants to the nutrient solution, consisting of intervals of 60, 30, and 15 minutes between pumping periods of 15 minutes; and uninterrupted flow of the nutrient solution. The plants were harvested at 30 days after transplanting, and 15 lettuce plants of each experimental plot were used to determine total fresh weight; root fresh weight; shoot freshweight; and contents of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, and Zn in shoots, roots, and in the diagnostic leaf; accumulation of these nutrients in shoots and roots; and nitrate and ammonium contents in plant shoot. The highest production and profitability of lettuce were found using uninterrupted nutrient solution flow, which provided higher shoot and root nutrient contents to plants, and resulted in a better nutrient use efficiency.